2002
DOI: 10.1021/jp020656+
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Emission Studies on Gold Nanoparticles

Abstract: We report the light emission decay in bare gold nanoparticles by using the fluorescence up-conversion technique. The emission decay, of which the time constants increase consistently with excitation intensity, closely follows the electron thermalization dynamics, which has been independently observed from the bleach recovery of the surface plasmon band under the identical experimental conditions. These results indicate that a weak light emission from relatively large gold nanoparticles is attributable to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
56
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 15 publications
8
56
2
Order By: Relevance
“…20,21 Here we describe the calculation of optical extinction spectra for octahedra dimers that will be used to interpret the experimental emission spectra. We assume the particles have a 60 nm edge length.…”
Section: Theorymentioning
confidence: 99%
“…20,21 Here we describe the calculation of optical extinction spectra for octahedra dimers that will be used to interpret the experimental emission spectra. We assume the particles have a 60 nm edge length.…”
Section: Theorymentioning
confidence: 99%
“…For one-photon luminescence (OPL) from metallic nanostructures excited by a CW laser, the Stokes emission band of nanostructures often resembles their scattering spectral line shape, which implies the strong correlation between the PL and the surface plasmon resonances. In contrast to the Stokes emission in the OPL, the anti-Stokes emission has a considerably different spectral profile but rarely receives attention, although it has been observed in the OPL of gold nanoparticles excited by a cw laser a decade ago [14]. The anti-Stokes emission has received considerable attention in two-photon luminescence (TPL) excited by a pulse laser.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated that green fluorescence could be emitted by AuNPs prepared in this work. Because the AuNPs about 5nm exhibit a relatively strong photoluminescence at 440 nm, the AuNPs in the diameter range 2–6 nanometer could emit green fluorescence …”
Section: Introductionmentioning
confidence: 99%